PROFISSIONAL BIOMÉDICO: HABILITAÇÕES - Rockenbach, Amanda Cecilia Winter; Silva, Isabel da; de Barros, Giovana Aparecida Borges; Hilgemberg, Glaucia Renee (Anais de Saúde Coletiva; v. 1 n. 1 (2021): 2021/2, 2021)
.